Lipopolysaccharide amplifies eosinophilic inflammation after segmental challenge with house dust mite in asthmatics. Issue 3 (31st December 2014) - Berger, M.; de Boer, J. D.; Bresser, P.; van der Poll, T.; Lutter, R.; Sterk, P. J.; van der Zee, J. S.
Abstract Background House dust contains mite allergens as well as bacterial products such as lipopolysaccharide (LPS). Asthma exacerbations are associated with the level of exposure to allergens and LPS. LPS can potentiate allergen effects in steroid‐naïve patients. Long‐acting β2‐agonists (LABA) were shown to inhibit LPS‐induced bronchial inflammation in healthy volunteers. The aim of this study was to assess the effect of LPS on the allergen‐induced eosinophilic inflammation [primary endpoints: eosinophil counts and eosinophil cationic protein (ECP)] induced by bronchial instillation of house dust mite (HDM) in patients with asthma on maintenance treatment with inhaled corticosteroids (ICS). Methods Thirty‐two nonsmoking asthmatics with HDM allergy were treated with run‐in medication (fluticasone propionate 100 μg bid) during 2 weeks before the study day. All patients underwent bronchial challenge with HDM, and half of them were randomized to receive additional LPS. Both groups were randomized to receive pretreatment with a single inhalation of 100 μg salmeterol 30 min before bronchial segmental challenge. Six hours later, bronchoalveolar lavage (BAL) was collected for leukocyte cell count, differentials, and cellular activation markers. Results Challenge with HDM/LPS induced a significant increase in eosinophil cationic protein (P = 0.036) and a trend toward an increase in BALF eosinophils as compared to HDM challenge. Conclusion Lipopolysaccharide promotes eosinophilic airway inflammation in patients with asthma despite being on maintenance treatment with ICS.